Optimizing the technique of anterior capsulorhexis in anterior capsule fibrosis - S. I. Nikolashin; E. S. Pirogova (Российский офтальмологический журнал)
Purpose. To optimize the technique for femtolaser-assisted anterior capsulorhexis in patients with anterior capsular fibrosis.   Material and methods.  All patients were divided into two groups: group I included 12 patients with central and peripheral anterior capsule fibrosis who underwent anterior circular capsulorhexis usingfemtolaser LensX (Alcon, USA) with laser energy 10 and 15 J . Group I I included 11 patients with central and peripheral anterior capsule fibrosis, who underwent manual capsulorhexis.   Results.  In group II, surgical complications occurred in 3 cases (27.3 %), group I was uneventful. In group I, BCVA increased to 0.80 (0.70; 0.85) over the 6 months’follow-up, in group II, it increased to 0.70 (0.60; 0.70) In group I, IOP was 16.4 (15.0; 17.4) mm Hg, in group IIit was 16.2 (13.8; 18.7) mm Hg.   Conclusion. Femtolaser-assisted anterior capsulorhexis in patients with anterior capsule fibrosis allowed reducing the number of operative complications by 27 % in comparison with manual capsulorhexis creation. Since even the maximum power values of the femtolaser system does not allow cutting the fibrotic capsule, we can make use of smaller power values, in particular 10 pJ, to create the anterior capsulorhexis in the area of unaffected or slightly fibrotic anterior capsule and cut the fibrotic part of the anterior capsule by collet scissors.